2009
DOI: 10.1091/mbc.e09-03-0221
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Size Provides Insights into the Function of Autophagy-related Proteins

Abstract: Autophagy is a major pathway of intracellular degradation mediated by formation of autophagosomes. Recently, autophagy was implicated in the degradation of intracellular bacteria, whose size often exceeds the capacity of normal autophagosomes. However, the adaptations of the autophagic machinery for sequestration of large cargos were unknown. Here we developed a yeast model system to study the effect of cargo size on the requirement of autophagy-related (Atg) proteins. We controlled the size of peroxisomes bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 56 publications
3
69
1
Order By: Relevance
“…Atg36 and PpAtg30 are receptors for pexophagy in S. cerevisiae and P. pastoris, respectively [143,144]. In both yeast and mammalian cells Pex3 and Pex14 function as cargo ligands [145,146].…”
Section: Pexophagymentioning
confidence: 99%
“…Atg36 and PpAtg30 are receptors for pexophagy in S. cerevisiae and P. pastoris, respectively [143,144]. In both yeast and mammalian cells Pex3 and Pex14 function as cargo ligands [145,146].…”
Section: Pexophagymentioning
confidence: 99%
“…The best described adaptor protein is yeast Atg11, involved in the Cvt pathway, 43 mitophagy 28,44 and pexophagy. 45 The Cvt pathway is a biosynthetic process involving transport of some vacuolar hydrolases (e.g. the precursor aminopeptidase 1 (prApe1) complex) from the cytosol to the vacuole.…”
Section: Adaptor Proteinsmentioning
confidence: 99%
“…46 Interestingly, increased Atg11 expression facilitates recruitment of Atg8 and Atg9 to the PAS and formation of more Cvt vesicles, suggesting that Atg11 can regulate the rate of selective autophagy. 10 Atg11 interacts also with the autophagy receptors Atg30 (pexophagy) 45 and Atg32 (mitophagy) 28,44 and likely has a similar role in selective autophagy of these cargo, but it is not required for non-selective starvation-induced autophagy.…”
Section: Adaptor Proteinsmentioning
confidence: 99%
“…Recently, we reported that yeasts from the order Saccharomycetales have either one large Atg28 protein or two smaller proteins, Atg29 and Atg31. 12 Here, we analyzed the genomes of the same eight yeasts and found that all contain a protein with the N-terminal RING and PHD fingers, either a longer Atg35 or a shorter Asr1 (see Fig. S1 in Sup.…”
Section: Introductionmentioning
confidence: 99%